Imigrantes negros africanos dos PALOP e negros brasileiros: a identidade étnica construída na imprensa de Portugal e do Brasil - Borges, Rosangela Ferreira de Carvalho (2008)
As its main purpose this thesis presents, not only how the ethnic identity of the African black immigrants from the PALOP -Portuguese-speaking African Countries - and their descendents is built in the Portuguese Newspapers Público, Correio da Manhã e O Expresso, in 2003, 2004 and 2005, as well as the ethnic identity of the Brazilian black men in the magazine Raça Brasil during the same period. It also aims at realizing both the case of the black Brazilians in Brazil and the black African immigrants from the PALOP living in Portugal which are the recurring themes, the proximities, the distances and resemblances that can be found in the Portuguese newspapers discourse and in the magazine Raça Brasil, although both are inserted in historical, social, politics, economic and cultural distinct realities. Defining this proposal , the investigation takes into account the theoretical contributions of the Max Weber, Fredrik Barth, Stuart Hall and Michel Wieviorka, as a means to capture the specifications of what is defined as an ethnic proper identity. The methodological option is the qualitative-quantitative approach through the content and discourse analysis by the use of the computer tool Statistical Package for Social Sciences SPSS, including interviews made with leaderships connected to the black African immigrants from the PALOP in Portugal and the black Brazilians in Brazil, which made it possible to conjugate different factor involved in the investigated reality. It also searches not to privilege just the results per se, but to enlighten the reflection about the relationship between the media, the ethnic identity and the private actions bonds and the context in which they occur